The Extent of Gambling in Kampala City - Ahaibwe, Gemma; Lakuma, Corti Paul; Katunze, Miriam; Mawejje, Joseph (Economic Policy Research Centre, 2016)
At a time when unemployment -particularly youth unemployment- is at its highest levels, there have been concerns that the youth have resorted to gambling as a source of livelihood. However, not so much empirical evidence existed to confirm these allegations regarding the level of participation and characteristics of gambling participants. This brief, based on a baseline survey conducted in Kampala city in April 2015, attempts to fill this vacuum by providing insights into the level of participation in the gambling industry. Survey findings show that gambling is prevalent at 24.3 percent among adults with sports betting as the most popular gambling activity. The majority of gambling participants gamble as a source of livelihood as opposed to leisure, and age, employment status and gender are major determinants in gambling participation. Finally, overall community reaction reflects a fairly negative perception on gambling.